New data on Rhyacophila (Trichoptera: Rhyacophilidae) from West Malaysia and Indonesia (Lombok and Bali) with descriptions of two new species - Ivanov, Vladimir D.; Melnitsky, Stanislav I. (Zootaxa, 2013)
A new species, Rhyacophila langkawia sp. n., belonging to the R. curvata Group sensu Schmid (1970) is described. The samples provide also material of the previously undescribed species cited by Schmid (1970) as R. schmidi, a nomen nudum; this species is described as R. schmidirossia sp. n., also in the R. curvata Group. Other sampled species were Rhyacophila curvata Morton, recorded for the first time from Negeri Sembilan (West Malaysia) and Lombok (Indonesia); Rhyacophila stheneboia Malicky & Prommi (Pahang and Negeri Sembilan, West Malaysia), and Rhyacophila anakbatukau Malicky, recorded for the first time from Lombok (Indonesia). Updated lists of the Rhyacophila species found inWest Malaysia andIndonesia are provided.